0262 Risk of miscarriage in association to work at night: a prospective payroll data study. (21st August 2017) - Begtrup, Luise Mølenberg; Specht, Ina Olmer; Hammer, Paula Edeusa Christina; Garde, Anne Helene; Hansen, Johnni; Bonde, Jens Peter Ellekilde
Abstract : The aim: An increased risk of miscarriage among fixed night workers has been reported, but exposure assessments have primarily been self-reported and often reported retrospectively. The aim of the study was to investigate, in a follow-up study with detailed data on exposure, whether working at night carries an increased risk of miscarriage. Design: The study population included all female public service employees in the five Danish administrative Regions, which were mainly hospital employees, with at least one pregnancy from 2007 through 2013 (n=21.920). Data on working time was extracted from the Danish Working Hour Database (DWHD), which holds detailed information on exact daily working hours. Night shift was defined as working at least three hours between 00:00 and 05:00. Information on miscarriages and births was obtained from The Danish National Patient Registry and The Medical Birth Registry. Risk of miscarriage was analysed according to the number of night shifts during the first trimester, accounting for maternal age, parity, socio-economic class, maternal smoking, BMI and induced abortions. Results: In this population 11.8% had had an abortion (n=2583). Compared to dayshift workers, the adjusted OR of miscarriage in women working 1–6, 7–12, 13–18, and 19+ nights during the first trimester of pregnancy was 0.93 (95% CI 0.78–1.11), 0.90 (95% CI 0.73–1.10), 0.66 (95% CI 0.47–0.94) and 0.96 (95% CI 0.64–1.45), respectively. Similar findings were found in analyses addressing night shifts during each month. Conclusion: We found no increased risk of miscarriage in night workers during the first trimester of pregnancy.